Development of charge level monitoring of lead-acid battery bank for PV system using fuzzy logic in LabView - Venancio, Leonardo A. (Animo Repository, 2019)
This paper presents a charge level monitoring system for lead acid battery bank in Solar Panel setup. The research implements the approximate linear relationship between the charge level and the current-voltage for lead acid batteries. Prediction method utilizes is the objective fuzzy logic approach. Both the interphase of the instrument and the fuzzy system together with the fuzzy rule system were created using LabView. Dataset used is based on an actual 12-hour data gathering of charging cycle and current-voltage readings. Simulation results show that the developed system generated correctly the charge level of the battery using only the instantaneous voltage and current readings from the sensors.